1990
DOI: 10.1016/s0022-5347(17)39388-6
|View full text |Cite
|
Sign up to set email alerts
|

The Urodynamic Consequences of Posterior Urethral Valves

Abstract: We evaluated urodynamically 41 patients with posterior urethral valves because of signs or symptoms of incontinence (35), frequency (3), hydronephrosis (2) and infection (1). Findings included normal urodynamic evaluations in 3 patients, 2 had high voiding pressures secondary to outlet resistance and 1 had incontinence on the basis of external urethral sphincter damage. In the remainder 3 patterns of bladder dysfunction were identified. Myogenic failure with overflow incontinence occurred in 14 patients. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(77 citation statements)
references
References 22 publications
4
70
1
2
Order By: Relevance
“…These studies further suggested that identical degrees of obstruction produced several different patterns of voiding dysfunction, each of which was associated with varying degrees of bladder weight increase. [32] and are also familiar to clinicians caring for men with prostatic obstruction [3,4]. Since the smallest degree of weight gain was found in association with high pressure voiding and the largest degree of weight gain was found in association with instability and decompensation, the results suggested to us that the response of the bladder to outflow obstruction might proceed along a continuum, characterized in its initial stages by high pressure voiding, and in later stages by instability and eventually decompensation.…”
Section: Methodsmentioning
confidence: 90%
“…These studies further suggested that identical degrees of obstruction produced several different patterns of voiding dysfunction, each of which was associated with varying degrees of bladder weight increase. [32] and are also familiar to clinicians caring for men with prostatic obstruction [3,4]. Since the smallest degree of weight gain was found in association with high pressure voiding and the largest degree of weight gain was found in association with instability and decompensation, the results suggested to us that the response of the bladder to outflow obstruction might proceed along a continuum, characterized in its initial stages by high pressure voiding, and in later stages by instability and eventually decompensation.…”
Section: Methodsmentioning
confidence: 90%
“…The description of the valve bladder syndrome by Peters is useful in following these patients long term [23]. Of course, all children with PUV are different and do not necessarily follow any schedule in terms of deteriorating bladder function, but it is clear that different patterns of bladder pathology are seen specifically in children with PUV.…”
Section: Long-term Managementmentioning
confidence: 99%
“…Even if bladder dysfunction due to valves can show different patterns [5] in response to the grade of detrusor hypertrophy induced by the obstruction, it has been suggested that the pattern in infancy and first years of life is characterized by hyper-contractility. This is recognized as over-activity during filling with frequent voidings and low bladder capacity [6].…”
Section: Introductionmentioning
confidence: 99%